A new species of Priochilus Banks, 1944 (Hymenoptera, Pompilidae, Pompilinae) from Panama - Wasbauer, Marius S.; Cambra, Roberto A.; Añino, Yostin J. (Zootaxa, 2017)
Priochilus chrysopygus Wasbauer, Cambra & Añino sp. nov. based on both sexes is described and illustrated. This new species is related to P. splendidulus (Fabricius). A short synopsis of biology in the genus Priochilus is given.